GAMBARAN PENGETAHUAN TENTANG ANEMIA DAN KEPATUHAN REMAJA DALAM MENGKONSUMSI TABLET TAMBAH DARAH - Gusti Ayu Nyoman Winda Sari Adnyana; Ni Wayan Armini; Ni Wayan Suarniti (Poltekkes Kemenkes Denpasar, 2021)
Anemia is one of the health problems in the world, the prevalence of anemia in young women aged 12-18 years reached 45.9% in Denpasar City in 2017. The purpose of this study in general is to know the description of knowledge and adherence of young women in consuming blood-added tablets in Dwijendra Junior High School in Denpasar in 2020. The research method used is a descriptive survey with cross sectional approach. The sampling technique is purposive sampling. By using primary data from the recapitulation of questionnaires distributed via Google form to 62 young women in Dwijendra Denpasar Middle School. Descriptive data analysis by describing knowledge about anemia and adolescent girls in consuming blood-added tablets in the frequency distribution table. The results showed that the majority of young women were in the category of good knowledge 48 respondents (78%) and less categories of 2 respondents (3%). Adherence of adolescent girls in consuming blood-added tablets is more likely to have low adherence as many as 38 respondents (61%), and high adherence only 4 people (7%). From this study, it was found that most of the well-informed young women about anemia had low adherence in consuming blood-added tablets.